Distinct 3-dimensional features of immature and mature dendritic cells - Khonlak, Manutsavee; Sanguansermsri, Donruedee; Pongcharoen, Sutatip; Wangteeraprasert, Apirath (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 2 (2023): April-June 2023DO - 10.14456/nujst.2023.19, 2023)
Dendritic cells (DCs) are interesting immune cells as they are antigen-presenting cells that initiate the adaptive immune response by T cells. The DCs are categorized as immature and mature DCs based on their morphology and cell surface molecules. In this present study, we employed 3-dimensional (3D) holotomography microscopy to study the morphology and intracellular lipid of DCs. The dendritic cells were derived from peripheral blood monocytes, which were purified from human buffy coats. Immature and mature DCs were characterized by flow cytometry using specific antibodies against cell surface molecules. The results showed that the mature DCs expressed a higher percentage of CD80 (61%) and CD86 (90%) than immature DCs (5% and 9%). Both immature and mature monocyte-derived DCs (mDCs) morphology and intracellular lipid were inspected using 3D holotomography microscopy. The mature mDCs had an increase in cell mass compared to immature mDCs, which were 651.52 + 43.34 and 465.51 + 97.87, respectively, p = 0.158). The mature mDCs also had an increase in lipid mass compared to immature mDCs, which were 186.57 + 29.53 and 2.07 + 0.32, respectively, p = 0.003).  The data based on this new 3D holotomography could help us extend our understanding of the morphological feature and intracellular lipid profiles of mDCs. Keywords : dendritic cells, 3-D image, holotomography